1988
DOI: 10.1135/cccc19882191
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational properties of surface hydroxyls: Nonempirical model calculations including anharmonicities

Abstract: Complete sets of harmonic, semidiagonal cubic as well as diagonal cubic and quartic force constants are reported for the internal coordinates of terminal, ≣SiOH, and bridging, ≣SiOH·Al≣, surface hydroxyls on silica and zeolites. They are obtained by numerical differentiation of analytically calculated gradients of the energy (SCF approximation, 6-31 G* basis set). A GF vibrational analysis is performed and after making a nonlinear transformation of the force constants into normal coordinates the anharmonicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The computed frequencies of 600 (438) cm −1 for Si2a–H(D) and 621 (422) cm −1 for the Si1a–H(D) modes agree with experiments within the accuracy of vibrational modes obtained by density functional theory (DFT)–generalized gradient approximation and the harmonic approximation. In fact, anharmonicities can change frequencies upto ~80 cm −1 for groups such as surface silanols40, which provides an indication of the accuracy of the present calculations. As evident from Table 1, the largest difference between experimental and theoretical values is 37 cm −1 , with the theoretical value always lower than the experimental one, indicating the systematic nature of this error.…”
Section: Resultsmentioning
confidence: 78%
“…The computed frequencies of 600 (438) cm −1 for Si2a–H(D) and 621 (422) cm −1 for the Si1a–H(D) modes agree with experiments within the accuracy of vibrational modes obtained by density functional theory (DFT)–generalized gradient approximation and the harmonic approximation. In fact, anharmonicities can change frequencies upto ~80 cm −1 for groups such as surface silanols40, which provides an indication of the accuracy of the present calculations. As evident from Table 1, the largest difference between experimental and theoretical values is 37 cm −1 , with the theoretical value always lower than the experimental one, indicating the systematic nature of this error.…”
Section: Resultsmentioning
confidence: 78%
“…At a bulk NHJNH4+ ratio between 0 and approximately 1, at least five types of ammonium species may exist for samples 3 and 4. We assign the signal at 6 = 6.9 to ammonium ions located in a supercage, since this signal is also observed for sample 1 where the ammonium ions are located in the supercages only.…”
Section: Resultsmentioning
confidence: 99%
“…In an ab initio study by Mix et al 48 the of the free zeolitic OH groups was found to be equal to -4 cm-'. This shows the contribution to the potential curve of the bending vibration from the H bonding to be harmonic with high precision.…”
Section: Resultsmentioning
confidence: 99%